Incremental Shuttle Walking Test Distance Is Reduced in Patients With Pulmonary Hypertension in World Health Organisation Functional Class I - Billings, Catherine G.; Lewis, Robert; Armstrong, Iain J.; Hurdman, Judith A.; Smith, Ian A.; Austin, Matthew; Elliot, Charlie A.; Charalampopoulos, Athanasios; Sabroe, Ian; Lawrie, Allan; Thompson, A. A. Roger; Condliffe, Robin; et al. (Frontiers in Medicine, 2018)
Background: There is increasing interest in screening for and diagnosing pulmonary hypertension earlier in the course of disease. However, there is limited data on cardiopulmonary abnormalities in patients with pulmonary hypertension newly diagnosed in World Health Organisation Function Class (WHO FC) I. Methods: Data were retrieved from the ASPIRE registry (Assessing the Spectrum of Pulmonary hypertension Identified at a REferral centre) for consecutive treatment naïve patients diagnosed with pulmonary hypertension by cardiac catheterisation between 2001-10 who underwent incremental shuttle walk exercise testing. Results: Eight hundred and ninety-five patients were diagnosed with Group 1-5 pulmonary hypertension. Despite the absence of symptoms, patients in WHO FC I (n=9) had a significant reduction in exercise capacity (Incremental shuttle walk distance percent predicted, (ISWD%pred) 65±13 %, Z score -1.77±1.05), and moderate pulmonary hypertension with a mean pulmonary artery pressure 38±12mmHg and pulmonary vascular resistance 4.7±6.5 Wood Units, despite a normal diffusion of carbon monoxide adjusted for age and sex (DLco)%pred 99±40%. Compared to patients in WHO FC I, patients in WHO FC II (n=162) had a lower ISWD%pred 43±22 and lower DLco%pred 65±21% despite having similar pulmonary hemodynamics. Conclusion: Our results demonstrate that patients with newly diagnosed pulmonary hypertension with no or minimal symptomatic limitation have a significant reduction of exercise capacity.